Reconceptualizing Interventions of Built Heritage - Mi Lin (A+BE: Architecture and the Built Environment)
This research aims to reveal and explore the commonalities and differences in the definition of interventions on built heritage between theory and practice, using new aspects—cultural values and attributes of cultural significance—to support the definition process. A comparative approach is employed to discuss how different interventions are defined in international doctrines and applied in a local project, including stakeholders’ perspectives.